Altering CO binding on gold cluster cations by Pd-doping. Issue 34 (21st August 2019) - Abdulhussein, Heider A.; Ferrari, Piero; Vanbuel, Jan; Heard, Christopher; Fielicke, André; Lievens, Peter; Janssens, Ewald; Johnston, Roy L.
Abstract : Pd plays a crucial role in enhancing CO adsorption strength, through both direct and indirect means. Abstract : The introduction of dopant atoms into metal nanoparticles is an effective way to control the interaction with adsorbate molecules and is important in many catalytic processes. In this work, experimental and theoretical evidence of the influence of Pd doping on the bonding between small cationic Au N + clusters and CO is presented. The CO adsorption is studied by combining low-pressure collision cell reactivity and infrared multiple photon dissociation spectroscopy experiments with density functional theory calculations. Measured dissociation rates of cluster–CO complexes ( N ≤ 21) allow the estimation of cluster–CO binding energies, showing that Pd doping increases the CO adsorption energy to an extent that is size-dependent. These trends are reproduced by theoretical calculations up to N = 13. In agreement with theory, measurements of the C–O vibrational frequency suggest that for the doped PdAu N −1 + ( N = 3–5, 11) clusters, CO adsorbs on an Au atom, while for N = 6–10 and N = 12–14, CO interacts directly with the Pd dopant. A pronounced red-shifting of the C–O vibrational frequency is observed when CO interacts directly with the Pd dopant, indicating a significant back-donation of electron charge from Pd to CO. In contrast, the blue-shifted frequencies, observed when CO interacts with an Au atom, indicate that σ-donation dominates the Au–CO interaction. Studying such systems at the sub-nanometre scale enables a fundamental comprehension of the interactions between adsorbates, dopants and the host (Au) species at the atomic level.